Behaviour of Li isotopes in leachate during granite weathering: the Xunwu profile, southeastern China - Liu, Qi; Zhang, Jun-Wen; Gao, Ting; Zhao, Zhi-Qi (Frontiers in Earth Science, 2025)
IntroductionLithium (Li) isotopes are powerful tracers of silicate weathering processes. However, the geochemical behavior of lithium isotopes in granite leachates remains unclear.MethodsHere we report Li isotope compositions of leachates from a granite weathering profile in southeastern China. The parameter tau (τSi and τAl) and the Chemical Index of Alteration (CIA) were also used to characterize weathering intensity and related geochemical processes.ResultsThe Li concentration in the leachate varied from 0.05 to 1.03 mg/kg, and the δ7Lileachate values were −15.0‰ to +6.0‰ (mean = −0.85‰, n = 28). Below 0.8 m depth, the leachate had similar Li isotopic composition (−0.80‰ to +6.0‰, mean = +2.5‰, n = 19) with parent granite (+3.7‰).DiscussionThe leachate δ7Li values exhibit distinct vertical variations, reflecting contrasting geochemical processes along the profile. Below 0.8 m, δ7Li values are comparable to those of the parent granite, indicating limited isotopic fractionation during early weathering process. In contrast, markedly lower δ7Li values above 0.8 m suggest the release of 6Li from the dissolution of secondary minerals. This interpretation is supported by increased τSi and τAl values and their negative correlations with δ7Lileachate, implying co-migration of 6Li, Si, and Al during mineral dissolution. A positive correlation between δ7Li and CIA in the upper profile further indicates enhanced secondary mineral dissolution under intensified weathering. Our results suggest that as weathering progressed, the Li isotopic composition of the leachate from the upper weathering profile became gradually heavier toward the top, positively correlating with weathering intensity and indicating the dissolution of surface secondary minerals under intense weathering conditions.